Capturing Initial Gaze Attraction in Branded Spaces Through VR Eye-Tracking Technology - Kim, Nayeon (International journal of human-computer interaction, 2025)
This paper leverages recent strides in virtual reality (VR) technology to dissect user gaze patterns and initial responses in a VR-based in-store environment, with a focus on how visual elements impact attention in Human-Computer Interaction (HCI). Specifically, this exploratory study focuses on brand-centric components such as logos and colors, while also considering individual variables such as gender and design background. Employing a mixed-methods approach, the research combines qualitative and quantitative tools. A VR-integrated eye-tracking system records how participants' gaze behaves in a virtual retail environment. The study collects data from 50 participants in four scenarios: a control store (Case 1), introduction of the brand's logo signage (Case 2), infusion of the brand's primary color (Case 3), and a fusion of logo and color (Case 4). Two key eye-tracking metrics-time to first fixation (TTFF) and first fixation duration (FFD)-are harnessed to scrutinize gaze behavior across elements such as wall color, logo signage, wall display fixtures, and media screens. The research unearths statistically significant effects of visual elements on gaze behavior, with particular emphasis on TTFF and FFD. Gender disparities come to light in Cases 2, 3, and 4, affecting FFD on wall color (AOI 1) and TTFF on brand logo signage (AOI 2) in Case 2. Moreover, disparities in design background surface in Cases 1 and 3. Complementing the eye-tracking data and post-experiment interviews capture users' initial gaze attraction and preferences, offering valuable insights into their rationale. In essence, this study underscores the transformative potential of VR technology and eye-tracking techniques in HCI and furnishes actionable insights for those seeking to elevate brand recognition and consumer engagement within immersive virtual retail settings.